Verso un nuovo dialogo filosofico tra profano e religioso (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Il “suono”: fenomeno comuno al metodo religioso e profano - 2. Tempo e trascendenza - 3. Sapere e non saputo, medesimo e indicibile - 4. Presenza assenza - 5. Il prima dopo.Towards a new philosophical dialogue between profane and religiousABSTRACT: Christian religious philosophy builts itself from a very precise idea of the mortality whose time cannot as such manifest the truth of human being. Profane philosophy, we are in the eighteenth century, Enlightenment, asserts itself as the antithesis of such construction. Truth of human being belongs exclusively to his mortality, that is to say a determination of time. Everything becomes “history”, in other words, truth of a temporality of which the Reason is reappropriated. Here is the primary sense of the Reason of Enlightenment. This article is a critical interrogation about this pure methodological question.